Clinical efficacy and drug resistance of ceftazidime-avibactam in the treatment of Carbapenem-resistant gram-negative bacilli infection - Xiao, Shuang; Fu, Qianwen; Miao, Youhan; Zhao, Manna; Lu, Shengwei; Xu, Jie; Zhao, Weifeng (Frontiers in Microbiology, 2023)
Objective: To examine the clinical efficacy, safety, and resistance of Ceftazidime-Avibactam (CAZ-AVI) in patients with Carbapenem-resistant Gram-negative bacilli (CR-GNB) infections.We retrospectively analyzed relevant data of CR-GNB infected patients receiving CAZ-AVI treatment, analyzed relevant factors affecting drug efficacy, and compared the efficacy and safety with patients receiving Polymyxin B treatment.Results: Totally 139 patients were included. Agranulocytosis, septic shock, SOFA score, and CAZ-AVI treatment course were independent risk factors affecting the prognosis of patients with CR-GNB infection treated with CAZ-AVI while prolonging the treatment course of CAZ-AVI was the only protective factor for bacterial clearance. The fundamental indicators showed no statistically significant differences between CAZ-AVI and Polymyxin B treatment groups. At the same time, the proportion of patients treated with monotherapy was significantly higher in the CAZ-AVI group than in the Polymyxin B group (37.2% vs. 8.9%, P < 0.05), the 30-day mortality rate of the CAZ-AVI treatment group (27.7% vs. 46.7%, P = 0.027) was lower than that of the Polymyxin B treatment group. The 30-day clinical cure rate (59.6% vs. 40% P = 0.030) and 14-day microbiological clearance rate (42.6% vs. 24.4%, P = 0.038) were significantly higher in the CAZ-AVI than in the Polymyxin B treatment group. 89 patients were monitored for CAZ-AVI resistance, and the total resistance rate was 14.6% (13/89). The resistance rates of Carbapenem-resistant Klebsiella pneumoniae (CRKP) and Carbapenem-resistant Pseudomonas aeruginosa (CRPA) to CAZ-AVI were 13.5% and 15.4%, respectively.: CAZ-AVI has shown high clinical efficacy and bacterial clearance in treating CR-GNB infections. Compared with Polymyxin B, CAZ-AVI significantly improved the outcome of mechanical ventilation in patients with septic shock, agranulocytosis, Intensive Care Unit (ICU) patients, bloodstream infection, and patients with SOFA score > 6, and had a lower incidence of adverse events. We monitored the emergence of CAZ-AVI resistance and should strengthen the monitoring of drug susceptibility in clinical practice and the rational selection of antibiotic regimens to delay the onset of resistance.